2010
DOI: 10.1007/978-3-642-15515-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Blended Clustering for Health Data Mining

Abstract: Abstract. Exploratory data analysis using data mining techniques is becoming more popular for investigating subtle relationships in health data, for which direct data collection trials would not be possible. Health data mining involving clustering for large complex data sets in such cases is often limited by insufficient key indicative variables. When a conventional clustering technique is then applied, the results may be too imprecise, or may be inappropriately clustered according to expectations. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our new approach compares cluster properties at adjacent consecutive k numbers (or a range over several values regarded as a reasonable number) as described in [18]. The underlying idea behind it is an analysis of the "movement" of objects between clusters, considered either forward from k to k+1 or backwards from k+1 to k groups.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Our new approach compares cluster properties at adjacent consecutive k numbers (or a range over several values regarded as a reasonable number) as described in [18]. The underlying idea behind it is an analysis of the "movement" of objects between clusters, considered either forward from k to k+1 or backwards from k+1 to k groups.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In their study [10] considered blended clustering in healthcare data mining. The research observed that in terms of hospital utilization in Australia, length of stay, legal status, age as well as economic situation has an effect in usage of health services.…”
Section: Literature Reviewmentioning
confidence: 99%